Cardiopulmonary limitation to endurance performance - Anderson, W.; Haykowsky, M. J.; Welsh, R.; Jones, R. L.
The maintenance of stroke volume over the ride indicates that systolic function was maintained through 2-3 hours of exhaustive exercise. Our negative findings as compared to previous research indicate that either the intensity or duration of the effort was not sufficient to stimulate cardiac fatigue, or that differences were due to the method of echo imaging (upright during exercise for the present investigation vs. supine at rest for previous work). Pulmonary gas exchange was impaired at the onset of exercise, but did not worsen over the ride. The increase in absolute physiological deadspace indicates that parts of the lung were receiving air, but inadequate blood flow. The mechanism for this mismatching in ventilation and blood flow is unknown, but interstitial edema has been proposed. However, the observation that the large pressure difference between the alveoli and the artery did not worsen with exercise suggests that the interstitial edema is unlikely.